The Influence of Service Quality and Store Atmosphere on Customer Satisfaction at Vocational High School Business Center in Cirebon - Sitta Nurhajijah; Isti Riana Dewi; Rohadatul Aisy (Manajemen Bisnis, 2022)
The purpose of this research was to find out the influence between service quality and the atmosphere of the store on customer satisfaction at the Business Center at a vocational high school in Lemahabang Cirebon. Research methods used are validity test, reliability test, and multiple Linear Regression. The analysis tool used is the SPSS tool. The results of this study explain the influence between service quality of the store and the atmosphere of the store on customer satisfaction. This indicates that there needs to be an improvement of services such as honest words and friendly behavior to improve the quality of store service and modify the temperature and layout of goods to be more varied to entice customers to feel happy and make more visits to support the success of the business. Keywords: service quality, store atmosphere, customer satisfaction